2016
DOI: 10.7863/ultra.15.10056
|View full text |Cite
|
Sign up to set email alerts
|

Liver and Spleen Stiffness Measurements by Point Shear Wave Elastography via Acoustic Radiation Force Impulse

Abstract: To our knowledge, this article is the first report of ARFI findings in a US population with chronic liver disease. Liver stiffness reproducibility was excellent, particularly in nonobese patients. Spleen stiffness reproducibility was excellent in those with larger spleens and therefore may be most useful in patients with cirrhosis and portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 24 publications
1
9
0
2
Order By: Relevance
“…There are several studies discussing the reproducibility of SWS measurement in the liver. Our estimate of the intraoperator ICC for the right hepatic lobe at 4 cm depth was similar to that of previous studies using ARFI [12, 35, 36], but our interoperator ICC was worse than that in the results of Woo et al [12] where SWS was measured nine times. Some studies [37, 38] have shown that five SWE measurements could be used instead of ten without a significant effect on diagnostic performance.…”
Section: Discussionsupporting
confidence: 84%
“…There are several studies discussing the reproducibility of SWS measurement in the liver. Our estimate of the intraoperator ICC for the right hepatic lobe at 4 cm depth was similar to that of previous studies using ARFI [12, 35, 36], but our interoperator ICC was worse than that in the results of Woo et al [12] where SWS was measured nine times. Some studies [37, 38] have shown that five SWE measurements could be used instead of ten without a significant effect on diagnostic performance.…”
Section: Discussionsupporting
confidence: 84%
“…14,29 Reliability and failure rate pSWE has shown excellent repeatability and reproducibility, with both reported intraobserver and interobserver intraclass correlation coefficients (ICCs) higher than 0.85. 41,42 The technique failure rate is low (1-2%). 43 Obesity is the main cause of failed or unreliable measurements of pSWE.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Therefore considerable intra-observer and inter-observer variability existed in elastography measurement and were reported in breast lesions 25 , circumscribed objects 26 , and potentially in our study. In order to avoid inter-observer variation, in the current study, the US procedure was performed by one physician and the images were interpreted by the same examiner, while inter-observer reproducibility for liver and spleen was reported to be excellent 27,28 .…”
Section: Discussionmentioning
confidence: 99%